The convergence of the corrosion-fatigue curve family and its applications in estimating the life lost of metals in fatigue experiments - Phuc, Phan Huu (Vietnam Journal of Mechanics, 1997)
An approach to establish the no corrosion - fatigue curve is introduced. Based on this new approach, equations that describe the heat effect and life lost when determining the fatigue strength of metals may be established, also the reliability of the traditional fatigue curve can be assessed.